Analisis Kebijakan Pemberdayaan Ibu Hamil dalam Deteksi Dini Komplikasi Kehamilan di Indonesia: Scoping Review - Waldatul Hamidah; Hardisman, Hardisman (Jurnal Siti Rufaidah, 2025)
Background: Maternal Mortality Rate (MMR) in Indonesia remains a significant health challenge, with the majority of deaths related to preventable pregnancy complications. Empowering pregnant women through increased knowledge and skills in early detection is a key strategy to encourage timely care seeking. Objective: To review and analyze policies and implementation of programs empowering pregnant women in early detection of complications in Indonesia over the past five years (2020–2025), including policy frameworks, implementation models, research findings related to impacts and barriers, and policy recommendations. Methods: A scoping review using the Population-Concept-Context (PCC) approach was conducted. The literature search included scientific publications, national policy documents, and program reports published between 2020–2025. Relevant works included quasi-experimental studies, program reports, and policy documents. Main results: Maternal empowerment programs are driven by national policies to improve maternal health literacy and reduce MMR. Implementation is often integrated into Pregnant Women's Classes (KIH) or through digital media. Educational interventions have shown significant improvements in maternal knowledge of danger signs, but challenges include the low quality and availability of educational materials, as well as issues with outreach to mothers in remote areas. Conclusion: Empowering pregnant women in early detection is an important policy initiative to reduce maternal mortality. However, standardization of the curriculum, strengthening the role of cadres, and increased digital support are needed to ensure equitable reach and effectiveness.